2018
DOI: 10.2169/internalmedicine.9243-17
|View full text |Cite
|
Sign up to set email alerts
|

In Paroxysmal Atrial Fibrillation Patients, the Neutrophil-to-lymphocyte Ratio Is Related to Thrombogenesis and More Closely Associated with Left Atrial Appendage Contraction than with the Left Atrial Body Function

Abstract: Objective The neutrophil-to-lymphocyte ratio (NLR) is an inflammation marker that can be used to detect atrial inflammatory changes, which may contribute to a reduced left atrial (LA) function and thrombosis. Our study aimed to determine whether or not the association of NLR with the LA appendage (LAA) function in relation to thrombogenesis differs from the association with the LA body function in paroxysmal atrial fibrillation (PAF) patients. Methods A total of 183 PAF patients were studied. The LA volume ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…Yalcin et al [ 13 ] found a similar significant association in a larger sample, and reported that a higher NLR was an independent risk factor for LAT in 309 patients with NVAF (OR 1.59). Fukuda et al [ 14 ] demonstrated that an elevated NLR was an independent risk factor for spontaneous echo contrast in TEE (OR 1.86) and had greater left atrial volume index, left atrial appendage area and left atrial appendage wall motion velocity during atrial contraction. This study revealed an association between NLR and the left atrial appendage function in relation to thrombogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Yalcin et al [ 13 ] found a similar significant association in a larger sample, and reported that a higher NLR was an independent risk factor for LAT in 309 patients with NVAF (OR 1.59). Fukuda et al [ 14 ] demonstrated that an elevated NLR was an independent risk factor for spontaneous echo contrast in TEE (OR 1.86) and had greater left atrial volume index, left atrial appendage area and left atrial appendage wall motion velocity during atrial contraction. This study revealed an association between NLR and the left atrial appendage function in relation to thrombogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…More prospective studies with larger samples are needed to further validate our findings. Secondly, besides LAD, other echocardiographic paramters for thromboembolic risk in AF patients, such as left atrial volume index, left atrial appendage area and left atrial appendage wall motion velocity, were not routinely measured in our center [ 31 ]. In addition, in the anticoagulated patients enrolled in our study, we did not have information about the quality of anticoagulant control (e.g.time in therapeutic range for patients receiving warfarin and actual intake of oral anticoagulants), which impact the risk of LAT.…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic echocardiography was performed for all participating patient with a Vivid E9 ultrasound system (GE Vingmed Ultrasound, Horten, Norway) equipped with an M5S phased array transducer (2.5-5.0 MHz), and all measurements followed the guideline of the American Society of Echocardiography (21). (Supplementary material provides measurement methods for more relevant indicators).…”
Section: Echocardiographymentioning
confidence: 99%